2005
DOI: 10.1097/00003446-200504000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sensorineural Hearing Loss and Personal Hearing Aids on Cortical Event-Related Potential and Behavioral Measures of Speech-Sound Processing

Abstract: These results suggest that hearing-impaired individuals' brains process speech stimuli with greater accuracy and in a more effective manner when these individuals use their personal hearing aids. This is especially true at the lower stimulus intensity. The effects of sensorineural hearing loss and personal hearing aids on cortical ERPs and behavioral measures of discrimination are dependent on the degree of sensorineural loss, the intensity of the stimuli, and the level of cortical auditory processing that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
1
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(117 citation statements)
references
References 29 publications
8
102
1
6
Order By: Relevance
“…Recent studies suggest that consonants and vowels have different representations in the central auditory system, both in laboratory animals (16) and in human beings (17) . In this study, results with the use of speech sounds suggest that CAEPs can be used as an objective tool to assess the characteristics of amplification and the validation of hearing-aid fittings, thus enabling the measurement of audibility of speech sound amplification among individuals who cannot collaborate, which is also stated by other authors (3,9,10,(18)(19)(20)(21) , who showed that the use of hearing aids improved the presence of measurable cortical responses (Table 1).…”
Section: Discussionsupporting
confidence: 71%
“…Recent studies suggest that consonants and vowels have different representations in the central auditory system, both in laboratory animals (16) and in human beings (17) . In this study, results with the use of speech sounds suggest that CAEPs can be used as an objective tool to assess the characteristics of amplification and the validation of hearing-aid fittings, thus enabling the measurement of audibility of speech sound amplification among individuals who cannot collaborate, which is also stated by other authors (3,9,10,(18)(19)(20)(21) , who showed that the use of hearing aids improved the presence of measurable cortical responses (Table 1).…”
Section: Discussionsupporting
confidence: 71%
“…The P1-N1-P2 response has been reliably evoked and recorded in individuals listening to speech (Friesen & Tremblay, 2006;Tremblay, Friesen, Martin, & Wright, 2003) and nonspeech stimuli (Segalowitz & Barnes, 1993;Walhovd & Fjell, 2002), and has been used to study the neural detection of acoustic change in a number of clinical populations, including older adults (Tremblay, Billings, & Rohila, 2004), children (Ponton, Eggermont, Kholsa, Kwong, & Don, 2002, individuals with hearing loss (Korczak, Kurtzberg, & Stapells, 2005), individuals with auditory neuropathy (Michalewski, Starr, Nguyen, Kong, & Zeng, 2005), and individuals with cochlear implants (Friesen & Tremblay, 2006 importantly, the P1-N1-P2 response corresponds well to the behavioral detection of frequency, intensity, and temporal changes in a stimulus (for review see Hyde, 1997), making it a particularly useful tool for the assessment of perception among patients who are unable to perform behavioral tasks.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…The N1 component is thought to reflect stimulus characteristics such as intensity and timing (Naatanen & Picton, 1987), and may be generated by activity in the superior temporal plane as well as other sources in the temporal and frontal lobes (Knight, Scabini, Woods, & Clayworth, 1988; Papanicolaou, Bau-mann, Rogers, Saydjari, Amparo, & Eisenberg, 1990;Scherg, Vajsar, & Picton, 1989). The P2 component also appears to be affected by stimulus characteristics such as frequency and intensity (Hegerl & Juckel, 1993;Hillyard & Picton, 1987;Novak, Ritter, & Vaughan, 1992), and has sources in the primary and secondary auditory cortices that may or may not be distinct from those of the N1 (Knight, et al, 1988;Zouridakis, Simos, & Papanicolaou, 1998).The P1-N1-P2 response has been reliably evoked and recorded in individuals listening to speech (Friesen & Tremblay, 2006;Tremblay, Friesen, Martin, & Wright, 2003) and nonspeech stimuli (Segalowitz & Barnes, 1993;Walhovd & Fjell, 2002), and has been used to study the neural detection of acoustic change in a number of clinical populations, including older adults (Tremblay, Billings, & Rohila, 2004), children (Ponton, Eggermont, Kholsa, Kwong, & Don, 2002, individuals with hearing loss (Korczak, Kurtzberg, & Stapells, 2005), individuals with auditory neuropathy (Michalewski, Starr, Nguyen, Kong, & Zeng, 2005), and individuals with cochlear implants (Friesen & Tremblay, 2006 importantly, the P1-N1-P2 response corresponds well to the behavioral detection of frequency, intensity, and temporal changes in a stimulus (for review see Hyde, 1997), making it a particularly useful tool for the assessment of perception among patients who are unable to perform behavioral tasks.CAEPs have been used to assess temporal resolution in three studies (Heinrich, Alain, & Schneider, 2004;Michalewski, et al, 2005;Pratt, Bleich, & Mittelman, 2005). Heinrich et al (2004) found that N1 and P2 responses were similar for near-threshold gap durations for both within-and across-channel conditions using very brief pure-tone markers.…”
mentioning
confidence: 99%
“…In practice, the use of speech stimuli in LLAEP examination helps to evaluate the auditory processing of acoustic and linguistic information. In addition, it sensitizes the study of the neural bases of speech detection and discrimination (9,10) . LLAEP are recorded and analyzed by a sequence of peaks with positive-negative polarity, i.e., P1, N1, P2, N2 and P3.…”
Section: Introductionmentioning
confidence: 99%